Urosepsis and abscess in an adult with a triplicated renal collecting system treated percutaneously and endoscopically - Ilona Pilosov Solomon, MD (Elsevier, 2022)
Ureteral triplication is an extremely rare congenital disorder of the urinary tract. A review of the literature has shown that only about 100 cases have been reported worldwide. We present a case of a 50-year-old female with a known complete ureteral duplication on the right side and incomplete ureteral triplication on the left side that presented with signs of sepsis accompanied by a tender left flank mass. A detailed evaluation including imaging studies and endoscopy revealed a middle moiety obstruction causing abscess formation in the collecting system. A connection between the mid and lower moieties was demonstrated through an upper calyx of the lower moiety. The abscess was drained, and the patient further underwent ureteral stents placement to both the mid and lower ureters.Following antimicrobial treatment and several weeks of maximal drainage, the connection between the moieties was obviated, with no further episodes of urinary tract infection documented in follow up.